Cyanophycin Modifications—Widening the Application Potential - Kwiatos, Natalia; Steinbüchel, Alexander (Frontiers in Bioengineering and Biotechnology, 2021)
A circular bioeconomy approach is essential to slow down the fearsome ongoing climate change. Replacing polymers derived from fossil fuels with biodegradable biobased polymers is one crucial part of this strategy. Cyanophycin is a polymer consisting of amino acids produced by microorganisms with many potential applications. It consists mainly of aspartic acid and arginine, however, its composition may be changed at the stage of production depending on the conditions of the polymerization reaction, as well as the characteristics of the enzyme cyanophycin synthetase which is the key enzyme of catalysis. Cyanophycin synthetases from many sources were expressed heterologously in bacteria, yeast and plants aiming at high yields of the polymer or introducing different amino acids into the structure. Furthermore, cyanophycin can be modified at the post production level by chemical and enzymatic methods. Such modifications accelerate the scientific progress towards the replacement of petroleum-based products. Cyanophycin was previously only little known and has now emerged to a large ‘family’ of polymers. In addition, cyanophycin can be combined with other compounds to yield hybrid materials. This short review summarizes all modifications of cyanophycin reported in literature until now for the cyanophycin variants, and it addresses their possible applications.